2019
DOI: 10.3390/app9061255
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of a Proposed Semi-Submersible Floating Platform with Different Numbers of Offset Columns Based on the DeepCwind Prototype for Improving the Wave-Resistance Ability

Abstract: DeepCwind semi-submersible floating offshore wind turbines have been widely examined, and in some countries this type of floating offshore wind turbine has been adopted in the construction of floating wind farms. However, the DeepCwind semi-submersible floating offshore wind turbines still experience large surge motion that limits their operational time. Therefore, in this study, a semi-submersible floating platform with different numbers of offset columns, but with the same total weight, based on the DeepCwin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…The base platform was designed to be a simple, generic floating platform. The design of this model was initially inspired by the DeepCwind tested prototype designs [19,20], then modified to suit materials, test components, and facility size. The geometry represents a simple light duty, multi-purposed platform, which could host many different offshore applications.…”
Section: Floating Platform Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The base platform was designed to be a simple, generic floating platform. The design of this model was initially inspired by the DeepCwind tested prototype designs [19,20], then modified to suit materials, test components, and facility size. The geometry represents a simple light duty, multi-purposed platform, which could host many different offshore applications.…”
Section: Floating Platform Designmentioning
confidence: 99%
“…Mathematical models have been developed to examine the dynamic motions of offshore structures in the past [15][16][17]. Additionally, simulations and experimental tests have been completed on offshore structures [18][19][20] however the majority take place in a wave tank or basin and are therefore only able to investigate wave loads. More recently, it has been recognized that it is necessary to consider both wave and wind loads, so recent testing has focused on both parameters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At deep water, the supporting structures for wind turbines are floating type, and the main typology are the Semi-Submersible (SS), the Tension Leg Platform (TLP), and the Spar Buoy (SB). Regarding the SS platform, several studies and projects are under development [3][4][5], and a review can be found in Liu et al (2016) [6], while for the TLP typology, most of the projects are still in the scale test phase [7][8][9][10]. Regarding the SB platform, several studies have been carried out in recent years on this typology [11][12][13][14][15] and in October 2017, the world's first floating wind farm, the 30 MW "Hywind Scotland," became operating (https://www.equinor.com).…”
Section: Introductionmentioning
confidence: 99%